OPTIMASI BIAYA PRODUKSI PADA PT. XYZ DENGAN PENGENDALIAN PERSEDIAAN BAHAN BAKU SODIUM TRYPOLYPHATE - Arif Budi Sulistyo; Toha Ikhsan; Pugy Gautama (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2023)
This study aims to compare the Economic Order Quantity and Just In Time inventory methods to determine which inventory management strategy is best for PT XYZ. Observation, documentation, and interviews are the data collection methods used in this study. EOQ Formula, Safety Stock, Reorder Point, and Just In Time Formula are the data analysis techniques used in this study. The findings show that the component cost of raw material inventory using the EOQ method, storage costs IDR 2,312/order, and total inventory costs IDR 16,775,553. The JIT method reveals that the total cost of inventory is IDR 1,798,711. An inventory system with JIT that only has an inventory cost of 1,798,711 can reduce costs by about 43% more effectively, according to JIT and EOQ studies. The findings show that the component cost of raw material inventory using the EOQ method, storage costs IDR 2,312/order, and total inventory costs IDR 16,775,553. The JIT method reveals that the total cost of inventory is IDR 1,798,711. An inventory system with JIT that only has an inventory cost of 1,798,711 can reduce costs by about 43% more effectively, according to JIT and EOQ studies.